Analysis of homologous recombination deficiency in prostate cancer - A. G. Iyevleva; S. N. Aleksakhina; A. P. Sokolenko; E. A. Otradnova; A. S. Nikitina; K. A. Kashko; M. V. Syomina; N. S. Morozova; A. D. Shestakova; E. Sh. Kuligina; E. N. Imyanitov (Сибирский онкологический журнал)
Background. Mutations in homologous recombination repair (HRR) genes (BRCA2, ATM, CHEK2, NBN, etc.) are found in 20–25 % of patients with metastatic prostate cancer (PC) and are an indication for prescription of PARP inhibitors. Sensitivity to these drugs results from homologous recombination deficiency (HRD) in the tumor. It is currently not fully elucidated which HRR genes besides BRCA1/2 cause HRD. The aim of the study was to evaluate the presence of homologous recombination deficiency in pc associated with mutations in different HRR genes. Material and methods. Paired tumor and normal DNA samples from 272 pc patients were examined using the HiSNP Ultra Panel v1.0 NGS panel (Nanodigmbio). Tumor copy number variation profiles were used to obtain the HRD score, which was determined as the unweighted sum of three characteristics: the number of chromosomal regions with loss of heterozygosity (LOH), large scale state transitions (LST), and telomeric allelic imbalances (TAI). HRD scores in different pc categories were compared using the Mann–Whitney test. Results. The studied case series included 58 pcs with pathogenic/ likely pathogenic mutations in at least one of 34 HRR genes, and 214 pcs without HRR mutations. The median HRD scores in the groups with BRCA2, ATM, CHEK2, other HRR mutations and without HRR mutations were 41, 22.5, 7.5, 7.5, 14 and 9, respectively. The HRD score was significantly higher in BRCA2-associated tumors than in other PC categories (p<0.01 for all comparisons), except in cases with atm mutations, where the difference did not reach formal significance (p=0.051). Homologous recombination deficiency, defined as HRD score ≥25, was observed in 19/58 (32.8 %) PCs with HRR mutations and 40/214 (18.7 %) tumors without HRR mutations (p=0.03). In tumors without HRR mutations, the HRD score was significantly higher in the presence of somatic TP53 mutations (p<0.0001). Conclusion. In contrast to BRCA2-associated PCs, most tumors with mutations in the CHEK2, NBN, BLM, FANCM, BRCA1 genes are not characterized by homologous recombination deficiency. in the case of ATM gene lesions, approximately half of pcs have a high HRD score. Testing for HRD score allows identification of a significant proportion (5–19 %, depending on the threshold chosen) of tumors with HRD among pcs that do not contain mutations in HRR genes.